Spectrum of Clinical Presentation of Tuberculosis Meningitis in Children at a Tertiary Care Hospital - Zulfiqar Ali, Abdul Rehman, Saba Bakht, Shagufta Niazi, Afsheen Oneeb, Tehmina Maqbool, Adeel Khalid Choudhary, (Pakistan Journal of Medical & Health Sciences, 2022)
In underdeveloped nations, TB in children is a major public health issue, with tubercular meningitis being a devastating consequence with high death rate. Tuberculous Meningitis (TBM) is caused by the spread of main or secondary pulmonary illness through the bloodstream. One of the most dangerous clinical symptoms of TB is infection of the central nervous system. The advanced stage of TBM may have a negative impact on the result. Objective: To determine frequency of different spectrum of clinical presentation of tuberculosis meningitis in children at tertiary care hospital Material and Methods: This was a cross sectional study carried out at the Children hospital and Institute of child health from May, 2018 to Nov, 2018. About 364 patients were employed in the research. Patients' or attendants' informed written consent was attained, and their demographic information (including name, age, gender, residence, and duration of pain) was recorded. All newly diagnosed cases were taken in this study for further investigation about their stages of the disease. All stages were labeled as per operational definition. Results: The patients' normal age was 6.56 SD 3.46 years, with the lowest and highest ages being 1 and 12 years, respectively. There were 200 male cases (54.9%) and 164 female cases (45.1%), with a larger male to female ratio. With a minimum and highest GCS score of 5 and 15, the mean GCS is 11.76 2.77. According to the operational definition, 30 patients (8.2%) had stage I TBM, 150 cases (41.2%) had stage II TBM, and 184 instances (50.5%) had stage III TBM. Conclusion: The outcomes of this study revealed that about half of the cases had stage III TBM, implying that patients with TBM should be managed properly if this stage is remembered. With aggressive and selective treatment plan the prognosis can be increased and rate of mortality may be decreased.